Broken : a novel - Slaughter, Karin, 1971- (New York : Delacorte Books, 2010)
When Special Agent Will Trent arrives in Grant County, Georgia, he finds a police department determined to protect its own and far too many unanswered questions about a prisoner's death and about a policewoman's role in the death of Grant County's popular police chief
Keywords: Linton, Sara (Fictitious character) -- Fiction; Policewomen -- Fiction; Georgia -- Fiction